Pre-treated Populus tomentiglandulosa extract inhibits neuronal loss and alleviates gliosis in the gerbil hippocampal CA1 area induced by transient global cerebral ischemia - Park, Joon Ha (Anat Cell Biol, 2017)
The genus Populus (poplar) belonging to the Salicaceae family has been used in traditional medicine, and its several species show various pharmacological properties including antioxidant and anti-inflammatory effects. No study regarding protective effects of Populus species against cerebral ischemia has been reported. Therefore, in the present study, we examined neuroprotective effects of ethanol extract from Populus tomentiglandulosa (Korea poplar) in the hippocampal cornu ammonis (CA1) area of gerbils subjected to 5 minutes of transient global cerebral ischemia. Pretreatment with 200 mg/kg of P. tomentiglandulosa extract effectively protected CA1 pyramidal neurons from transient global cerebral ischemia. In addition, glial fibrillary acidic protein immunoreactive astrocytes and ionized calcium binding adapter molecule 1 immunoreactive microglia were significantly diminished in the ischemic CA1 area by pretreatment with 200 mg/kg of P. tomentiglandulosa extract. Briefly, our results indicate that pretreatment with P. tomentiglandulosa extract protects neurons from transient cerebral ischemic injury and diminish cerebral ischemia-induced reactive gliosis in ischemic CA1 area. Based on these results, we suggest that P. tomentiglandulosa can be used as a potential candidate for prevention of ischemic injury.